High Hydration Factor in Older Hispanic-American Adults: Possible Implications for Accurate Body Composition Estimates - González Arellanes, Rogelio; Urquidez Romero, Rene; Rodriguez-Tadeo, Alejandra; Esparza Romero, Julian; Mendez Estrada, Rosa O; Ramırez Lopez, Erik; Robles Sardin, Alma E; Pacheco Moreno, Bertha E; Alemán Mateo, Heliodoro (MDPI, 2020)
Age- and obesity-related body composition changes could influence the hydration factor (HF) and, as a result, body composition estimates derived from hydrometry. The aim of the present study was to compare the HF in older Hispanic-American adults to some published values. This cross-sectional study included a sample of 412 subjects, men and women, aged ≥60 years from northern Mexico. HF values were calculated based on the ratio of total body water-using the deuterium dilution technique-to fat-free mass, derived from the four-compartment model. The mean HF value for the total sample (0.748 ± 0.034) was statistically (p ≤ 0.01) higher than the traditionally assumed value of 0.732 derived from chemical analysis, the “grand mean” value of 0.725 derived from in vivo methods, and the 0.734 value calculated for older French adults via the three-compartment model. The HF of the older women did not differ across the fat mass index categories, but in men the obese group was lower than the normal and excess fat groups. The hydration factor calculated for the total sample of older Hispanic-American people is higher than the HF values reported in the literature. Therefore, the indiscriminate use of these assumed values could produce inaccurate body composition estimates in older Hispanic-American people.